Diet-dependent fecundity of the spiders Atypena formosana and Pardosa pseudoannulata, predators in irrigated rice - Sigsgaard, Lene; Toft, Søren; Villareal, Sylvia (Wiley, 2001)
1 The fecundity of the spiders Atypena formosana and Pardosa pseudoannulata was assessed on diets of brown planthopper Nilaparvata lugens (BPH), green leafhopper Nephotettix virescens (GLH), Collembola (Entomobryidae), Droso phila melanogaster and three prey mixtures; BPH–GLH, BPH–GLH–Collembola and a full mixed diet of BPH–GLH–Collembola–D. melanogaster.2 Egg production and hatching success was high in A. formosana except on the BPH, the GLH and the BPH–GLH diets. In P. pseudoannulata egg production and hatching success was lowest on diets of GLH and BPH–GLH, whereas this spider used BPH better.3 Differences between offspring sizes were small.4 Survival of A. formosana females was lowest on the GLH and BPH–GLH diets. In P. pseudoannulata survival did not differ significantly.5 Food conversion efficiency was highest on the Collembola and the D. melanogaster diets for both spiders.6 Overall, diets of Collembola and D. melanogaster had the highest quality for both spiders, the BPH–GLH–Collembola and the full mixed diets were intermediate in quality, the quality of the BPH diet was intermediate to low and quality of the GLH and BPH–GLH diets was low.7 There need not be a contradiction between low dietary value of hoppers and successful natural biological control provided that the nutritional needs of the spiders are met by sufficient alternative prey.8 The hopper‐spider relationship is comparable to that of aphids and spiders in temperate cereals, suggesting that low dietary quality of Homopterans to spiders may be widespread.